(untitled) (ModaPalavra e-periódico, 2024)
Fashion indicates ways of life and inspires changes in behavior, consumption and in the various material structures that circumscribe human existence, particularly the relationship between body and clothing. Therefore, social and emotional complementarity is assumed, awakened through symbolic systems. The socially integrated body assimilates the symbolism of the collective in which it is inserted, a precursor situation of differences and social bond. Symbolic assumptions are also justified in audiovisual productions, which seek to represent different meanings and experiences. This article aims to understand the translations between these two poles: culturally clothed body and diegetic effects of costumes. A qualitative work that, through film analysis, decomposes the narrative strategies in the dramatic structure of the miniseries Transatlântico (Netflix, 2023). To do so, it uses a bibliographic review of the field of fashion in clothing and the scope of socially instituted sensibilities, in order to link effects and consequences of these to audiovisual production.